Wpływ diety na występowanie chorób nowotworowych = The impact of diet on the occurrence of tumor diseases - Pudło, Hanna; Respondek, Malwina; Szefczyk-Polowczyk, Lucyna; Wengel-Woźny, Karina (Journal of Education, Health and Sport, 2015)
Pudło Hanna, Respondek Malwina, Szefczyk-Polowczyk Lucyna, Wengel-Woźny Karina. Wpływ diety na występowanie chorób nowotworowych = The impact of diet on the occurrence of tumor diseases. Journal of Education, Health and Sport. 2015;5(9):549-558. ISSN 2391-8306. DOI10.5281/zenodo.31473 http://dx.doi.org/10.5281/zenodo.31473 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A549-558 https://pbn.nauka.gov.pl/works/635198 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 26.08.2015. Revised 05.09.2015. Accepted: 27.09.2015. Wpływ diety na występowanie chorób nowotworowych The impact of diet on the occurrence of tumor diseases Hanna Pudło1, Malwina Respondek1, Lucyna Szefczyk-Polowczyk2, Karina Wengel-Woźny3 1Śląski Uniwersytet Medyczny w Katowicach, Studium Doktoranckie Wydział Zdrowia Publicznego w Bytomiu, Polska 2Śląski Uniwersytet Medyczny w Katowicach, Studium Doktoranckie Wydział Farmaceutyczny z Oddziałem Medycyny Laboratoryjnej w Sosnowcu, Polska 3Śląski Uniwersytet Medyczny w Katowicach, Studium Doktoranckie Wydział Nauk o Zdrowiu w Katowicach, Polska 1Medical University of Silesia, Ph.D. Department of Public Health in Bytom, Poland 2Medical University of Silesia, Ph.D. Department of Pharmacy with the Divisionof Laboratory Medicine in Sosnowiec, Poland 3Medical University of Silesia, Ph.D. Department of Health Sciences in Katowice, Poland 3 Słowa kluczowe: dieta, nowotwory, zachorowanie. Key words: diet, cancer, disease. Streszczenie Od wielu lat w Polsce obserwuje się szybki wzrost zachorowań na nowotwory. Zachorowalność na nowotwory wzrasta na całym świecie. Komitet Ekspertów WHO, podsumowując stan wiedzy o epidemiologii nowotworów złośliwych, stwierdził, że znaczna ich część jest wynikiem stylu życia i środowiska. Ocenia się, że ok. 20–30 % wszystkich nowotworów złośliwych to nowotwory dietozależne, w rozwoju których istotne znaczenie mają czynniki żywieniowe. Celem pracy jest analiza żywieniowych czynników występowania nowotworów oraz identyfikacja zagrożeń wynikających z diety. Znajomość czynników ryzyka występowania raka może umożliwić stworzenie zaleceń żywieniowych w terapii antynowotworowej. Liczne badania potwierdzają wpływ diety na powstawanie oraz rozwój choroby nowotworowej dlatego istotna wydaje się profilaktyka chorób nowotworowych poprzez szerzenie wiedzy na temat właściwych zachowań zdrowotnych, w tym również odpowiednich nawyków żywieniowych. Ryzyko występowania raka może być modyfikowane poprzez m. in utrzymanie prawidłowej masy ciała, spożywania odpowiedniej ilości warzyw i owoców, unikanie alkoholu. Należy dążyć do wprowadzania edukacji żywieniowej już u dzieci i młodzieży co może pozwolić na ograniczenie występowania nowotworów dieto zależnych. Badania dowodzą, że osoby z wysokim poziomem wiedzy na temat profilaktyki chorób nowotworowych podejmują korzystniejsze zachowania zdrowotne. Abstract For many years Poland has seen a rapid increase in the incidence of cancer. The incidence of cancer is increasing worldwide. WHO Expert Committee, summing up the state of knowledge about the epidemiology of malignant tumors, said that much of it is the result of lifestyle and environment. It is estimated that approx. 20-30% of all malignant cancers diet related, the development of which are important nutritional factors. The aim of the study was to analyze the nutritional factors for the appearance of cancer and the identification of risks from the diet. Knowledge of the risk factors for cancer may enable the creation of the Dietary Guidelines for antitumor therapy. Numerous studies confirm the impact of diet on the formation and progression of cancer because it seems relevant to the prevention of cancer by raising awareness about relevant health behaviors, including proper eating habits. The risk of cancer can be modified by m. In maintaining a healthy body weight, eating the right amount of fruits and vegetables, avoiding alcohol. The aim should be to introduce nutritional education already in children and adolescents which could eventually allow the reduction of tumors diethoxy subsidiaries. Studies have shown that people with high levels of knowledge about cancer prevention undertake more favorable health behavior.